1995
DOI: 10.1111/j.2042-7174.1995.tb00819.x
|View full text |Cite
|
Sign up to set email alerts
|

Family health services authorities and community pharmacists at the purchaser-provider interface

Abstract: The views of both purchasers (family health services authorities [FHSAs]) and providers (community pharmacists) were sought on the development of community pharmaceutical services in the light of the 1992 pharmaceutical care report. Questionnaires were posted to the 480 pharmacists in charge of all community pharmacies in Wessex and to the 98 general managers of FHSAs in England and Wales. The questionnaires focused on reactions to those recommendations of the pharmaceutical care report which, if implemented, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…However, similar studies have also found remuneration to be an important issue. [6][7][8][9][10][11][12] Contractors are remunerated in the UK, as in many other countries, mainly on a fee for item of service basis, related to the number of prescriptions dispensed, although a practice allowance is also payable provided certain conditions are met. Some interviewees expressed the view that to an extent Scottish pharmacists were already paid for providing pharmaceutical care through these mechanisms, although the need for changes to both the remuneration structure and terms of the NHS contract was highlighted by many.…”
Section: "Repeat Dispensing Systems Are a Vehicle Bymentioning
confidence: 99%
“…However, similar studies have also found remuneration to be an important issue. [6][7][8][9][10][11][12] Contractors are remunerated in the UK, as in many other countries, mainly on a fee for item of service basis, related to the number of prescriptions dispensed, although a practice allowance is also payable provided certain conditions are met. Some interviewees expressed the view that to an extent Scottish pharmacists were already paid for providing pharmaceutical care through these mechanisms, although the need for changes to both the remuneration structure and terms of the NHS contract was highlighted by many.…”
Section: "Repeat Dispensing Systems Are a Vehicle Bymentioning
confidence: 99%
“…The Government endorsed the extended role concept (DHSS 1988), and a subsequent joint report, by the Department of Health and representative pharmaceutical bodies, on the future of community pharmacy in the health service, assumed that the concept would be fully embraced by pharmacists (Royal Pharmaceutical Society of Great Britain 1992). In addition, the remuneration procedure for community pharmacists was changed to permit payment to pharmacists for additional services, such as locally negotiated services to residential homes (Hunt et al 1995).…”
Section: Introductionmentioning
confidence: 99%